Lotus fiber-derived scaffolds for enhanced cultured meat production: Quality and sustainability - Yueren Wu; Yajun Li; Qing Yang; Chaoyong He; Jianping Tang; Liyang Shi; Jianwu Dai; Can Zhang (Bioactive Materials)
The expanding global population intensifies demand for sustainable protein sources. Cell-cultured meat (CM) offers a promising alternative to conventional meat production but faces challenges in scalability and food-grade scaffold design. Current scaffolds often fail to replicate muscle tissue's structural and mechanical properties or support large-scale CM production. Moreover, the sensory and nutritional qualities of CM remain understudied. Here, we developed a novel lotus fiber-based natural plant fiber (NPF) scaffold mimicking native muscle tissue architecture. Porcine muscle stem cells (pMuSCs) were cultured on the NPF scaffold (pMuSCs-NPF), and their viability, proliferation, and differentiation were evaluated. The NPF scaffolds exhibited high biocompatibility and promoted pMuSCs alignment and differentiation into organized myotubes, as evidenced by enhanced expression of myogenic markers (MYOD, MYOG, MyHC) and extracellular matrix (ECM) components (desmin, fibronectin). Multi-omics analyses revealed substantial upregulation of genes and proteins associated with muscle development and ECM remodeling in pMuSCs-NPF compared to conventional plastic culture. Sensory and nutritional analyses indicated that the resulting CM closely resembled traditional meat in appearance, texture, and nutritional profile, with comparable levels of protein and essential amino acids. Moreover, the NPF scaffold demonstrated scalability and supported adipogenic differentiation, which is vital for imparting meat-like flavor and texture. These findings establish NPF scaffolds as a viable and cost-effective platform for sustainable CM cultivation.